2020
DOI: 10.1186/s12883-020-01679-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphous low-grade neuroepithelial tumor of the young: case report and review focus on the radiological features and genetic alterations

Abstract: Background: A new type of epileptogenic tumor, the polymorphous low-grade neuroepithelial tumor of the young (PLNTY) was firstly reported by Jason T. Huse et al. at 2016. After that, only 1 case of PLNTY was reported by article. The radiological characteristics of PLNTY have not been concluded. The objective of our study was to report 3 cases of PLNTYs in details and to analyze the image characteristics and genetic alterations of PLNTYs by reviewing our cases and articles. Case presentation: There were 3 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 15 publications
0
53
0
Order By: Relevance
“…The unusual age of onset of the present case led us to critically perform a literature review and we found that, since its first description,[ 18 ] few cases of PLNTY have been reported in the English literature, mostly in the form of single case or small case series,[ 6 , 8 , 12 , 14 , 15 , 19 , 21 , 26 , 28 , 30 ] and almost all cases have been described in children and young adults;[ 6 , 8 , 12 , 14 , 15 , 19 , 21 , 28 , 30 ] the main findings of the literature review are summarized in [ Table 1 ]. Apart from the present case, to the best of our knowledge, only one case has been documented in a middle-aged adult patient by Riva et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The unusual age of onset of the present case led us to critically perform a literature review and we found that, since its first description,[ 18 ] few cases of PLNTY have been reported in the English literature, mostly in the form of single case or small case series,[ 6 , 8 , 12 , 14 , 15 , 19 , 21 , 26 , 28 , 30 ] and almost all cases have been described in children and young adults;[ 6 , 8 , 12 , 14 , 15 , 19 , 21 , 28 , 30 ] the main findings of the literature review are summarized in [ Table 1 ]. Apart from the present case, to the best of our knowledge, only one case has been documented in a middle-aged adult patient by Riva et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] The term “polymorphous low-grade neuroepithelial tumor of the young (PLNTY)” indicates a recently introduced epileptogenic neoplasm, first described in 2017 by Huse et al .,[ 18 ] affecting children and young adults and almost invariably characterized by oligodendroglioma-like histological appearance, diffuse cluster of differentiation-34 (CD34) immunohistochemical expression, and MAP kinase pathway-related molecular aberrations. [ 18 ] Since then, few other cases of PLNTY have been reported in the literature,[ 6 , 8 , 12 , 14 , 15 , 19 , 21 , 26 , 28 , 30 ] all in the form of single case reports or short case series, and most of them included children or young adults. [ 6 , 8 , 12 , 14 , 15 , 19 , 21 , 28 , 30 ] The temporal lobe is the most frequently affected site and epilepsy is the most common presenting symptom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty cases of PLNTY have been described to date, with the first ten reported by Huse et al in 2017 [ 3 , 5 , 9 , 10 , 16 , 21 , 27 , 28 ]; BRAF V600E mutation was seen in 14 of the patients and BRAF fusion in 1 patient. These BRAF alterations were mutually exclusive with other genomic events, including FGFR3 - TACC3 fusion, FGFR3 amplification, FGFR2 - CTNNA3 fusion, FGFR2 - INA fusion, FGFR2 - KIAA1598 fusion, FGFR2 rearrangement, and NTRK2 disruption, suggesting that the vast majority of PLNTYs are induced by BRAF mutation or FGFR fusion and subsequent MAPK activation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on its histological and genomic profiles, cIMPACT-NOW Update 6 recommends PLNTY as a possible future classification for pediatric-type glial/glioneuronal tumors. However, because of their rare etiology, only a few PLNTYs have been described to date [3,5,9,10,16,21,27,28], and it is unclear how genomic alterations promote the pathogenesis of the disease. Herein, we present a case of PLNTY with unique metabolic imaging features.…”
Section: Introductionmentioning
confidence: 99%